Pemberdayaan dan Pendidikan Melalui Sosialisasi Sibongsor Pada Masyarakat Dalam Upaya Pencegahan Stunting di Desa Cipurut Kecamatan Cireunghas - Mugni, Rafi Abdul; Isnaini, Abadila; Alyarizki, Ajeng Suci (Universitas Muhammadiyah Sukabumi, 2023)
Empowerment and Education of Sibongsor socialization to the community to prevent stunting is one solution to the problems faced by Cipurut Village, Cireunghas District, Sukabumi Regency, namely the low understanding of stunting in the community. The purpose of this activity is community empowerment regarding the understanding of stunting through sibongsor. The method of implementing this activity is community empowerment carried out by academics and students of Muhammadiyah Sukabumi University. The partner in this empowerment activity is Cipurut Village, Cireunghas District, Sukabumi Regency. The result of this empowerment is increased community knowledge in stunting prevention. The evaluation is carried out by looking at the target achievement of the empowerment program, where the community better understands the treatment of children affected by stunting.